Implementation of Health Insurance Policy for Poor Community Services in Enrekang Regency, South Sulawesi - Muliani S., Nurjannah Nonci, Hasmiati; Anggung Angreany (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to analyze the implementation of the Health Insurance Policy Towards Poor Health Services in Enrekang District, especially at the Massenrempulu Hospital, Enrekang Regency. The total population in this study was 2,366 participants in the National Health Insurance for inpatients and a sample of 96 participants for the National Health Insurance. The sampling technique used probability sampling using the random sampling method. Data collection techniques using observation, interviews, questionnaires (questionnaire) and documentation. The data obtained were analyzed with quantitative descriptive techniques with the help of SPSS 21.0 program. The results showed that: 1) The implementation of the health insurance policy especially Law Number 24 of 2011 reached an average percentage of 72.5% with a right category, according to researchers’ observations that the implementation of Law number 24 of 2011 implemented well, this means that if the implementation of the Act s carried out well, it means that the health service is running as expected; 2) Health Social Security Administering Agency Services reach an average percentage of 71.8% with good indicators. The implementation of health services by the Health Social Security Organizing Agency runs well, and this means it can meet the minimum standards of public service 3) The implementation of Law number 24 of 2011 statistically and jointly influences the service of the Health Social Security Administering Body. This same as the data is obtained in the field that the implementation of the Law has been implemented well.